The monetary policy transmission mechanism based macroeconomic model of north sumatera: a projection using stochastic simulation - Dede Ruslan (Proceedings of AICS - Social Sciences, 2017)
This paper analyses monetary transmission mechanism by using macroeconomic model north Sumatera, focusing especially on how the aggregate economy North Sumatera responds changes of interest rate.  In  this  paper,  we  establish  identification  conditions macroeconomics model  to  uncover the  effects  of monetary  policy to aggregate economy North Sumatera Utara.  By using semiannual data over the period 2000S1-2015S2 macroeconomics model is developed to analyze various channels of monetary policy mechanism in North Sumatera.  The empirical results show the strength and working of the monetary transmission mechanism is highly dependent on the balance-sheet compositions of the central bank, banks, firms and households. In the 3SLS model, changes of interest rate significantly affect the aggregate economic activity in North Sumatra through the mechanism of the magnitude of the elasticity of that occurs.